2011
DOI: 10.1080/14733145.2011.546072
|View full text |Cite
|
Sign up to set email alerts
|

Narrative case study research: On endings and six session reviews

Abstract: Background: An in-depth, small scale narrative inquiry into ex-clients' experiences of counselling was undertaken, using a local community counselling agency which highlighted several important themes, including reviews and endings. Aim: To show clients' lived experience of reviews and endings. Methods: Narrative case study methods were used, alongside researcher reflexivity. The meanings were co-constructed between the ex-clients, their counsellors and the researchers. Results: Clients stories show the inter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 24 publications
2
34
0
5
Order By: Relevance
“…Bringing the process to an end involved discussing what support they would need, allowing the participant to reflect on how far they had come and to recognise that they were ready to leave. Being free to return at a future date was valued by all of the participants, fitting with other findings recently published (Etherington & Bridges, ), even though they were aware they may not see the same therapist.…”
Section: Discussionsupporting
confidence: 85%
“…Bringing the process to an end involved discussing what support they would need, allowing the participant to reflect on how far they had come and to recognise that they were ready to leave. Being free to return at a future date was valued by all of the participants, fitting with other findings recently published (Etherington & Bridges, ), even though they were aware they may not see the same therapist.…”
Section: Discussionsupporting
confidence: 85%
“…To receive such an invitation seems, for most clients, to be experienced as a relief, which contributes to making them feel safe and personally affirmed, and reduces their fear of relapse. This is in line with Etherington and Bridges' (2011) findings of clients' valuing mutuality and negotiation in decision making about endings.…”
Section: Discussionsupporting
confidence: 75%
“…Knox et al (2011) found that clients with experience of a positive termination reported a strong therapeutic relationship and positive outcomes of therapy. In a qualitative study of clients' experiences of ending therapy, Etherington and Bridges (2011) recognized the therapeutic importance of mutuality and negotiation in decision making about endings. A qualitative study of the termination of open-ended and publicly funded psychotherapy found that clients and therapists seemed to share an ideal of reaching a concerted decision to end therapy (anonymized reference); through careful negotiation of when and how to end, they seemed to regulate their own and each other's mixed emotions about terminating and the upcoming separation.…”
mentioning
confidence: 99%
“…Maroda believes that an important skill for therapists to acquire is the careful listening to and tracking of the client's responses. While regular client reviews can be helpful (Etherington & Bridges, 2011) Maroda has in mind the therapist's careful examination of what they actually said, including the tone, the pace and the feelings associated with this. Therapists only need to listen to a recording (sound or vision) of their work to see how often we miss a client and how vital an empathic attunement that unconsciously matches early attachment patterns can be (McCluskey, 2005).…”
Section: Book Review Essaysmentioning
confidence: 99%